ORAL HEALTH PROBLEMS, HEALTHCARE INSURANCE AND ORAL HEALTH CARE SPENDING AMONG THE ELDERLY PATIENTS IN ROMANIA - Daniela Druguș; Corina Ciupilan; Dana Gabriela Budală; Amelia Surdu; Mihaela Monica Scutariu (Romanian Society of Oral Rehabilitation, 2022)
Introduction. According to World Health Organization reports at a global level, the percentage of coverage for oral health services offered by different countries varies between 40% and 80% for adults and there is an inverse correlation between the national income level and the mean oral health care spending through public health insurance Public health insurance is available in Romania, as it is in many other European nations, and is paid for by taxes. All children and young people under the age of eighteen, all employees, and all retirees are required to have health insurance, and this insurance must cover medical care received at any public hospital or clinic, as well as any private hospital or clinic that chooses to work with the National Health Insurance House and submit claims for reimbursement through this agency.